VD_FINDINFO Arrêt / 2010 / 735 vom 16. April 2010 - VD Tribunal cantonal (2010)
RENTE D'INVALIDITÉ, RÉVISION DE LA RENTE, REVENU D'INVALIDE, RECONSIDÉRATION | 28 al. 1 LAI, 28 al. 2 LAI, 28a LAI, 16 LPGA, 53 al. 2 LPGA, 117 al. 1 LPA-VD, 93 al. 1 let. a LPA-VD